Leiomyoma in the space of Retzius: a rare location - ., Shweta; Anjum, Shaheen; Mohsin, Zehra; Anees, Afzal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Extrauterine locations of leiomyomas are extremely rare clinical conditions as in the case of space of Retzius. Space of Retzius is a small anatomical compartment located posterior to the pubic symphysis and anterior to the urinary bladder. Here authors report a very unique case of 22-year-old woman presented to the study hospital with complaints of inability to conceive and difficulty in urination. Clinical examination and imaging of pelvis suggest leiomyoma of uterus located between lower part of anterior uterine wall and bladder. An attempt to remove the tumour laparoscopically was taken but later it was converted into open laparotomy due to unusual location of leiomyoma. Histopathology revealed the tumour to be a leiomyoma.